Association of early versus late care seeking for sport-related concussion in adolescent athletes in Canada: a historical cohort study - Sheilah Hogg-Johnson; Carolina Cancelliere; Cameron Marshall; Darrin Germann; Mohsen Kazemi; David Youngwoo Oh (BMJ Open Sport & Exercise Medicine)
Objectives This study aims to examine the association of time to recovery between early versus late presentation to outpatient community-based concussion management clinics following sport-related concussion (SRC) among adolescent Canadian athletes.Methods Using electronic health records (between January 2017 and December 2019) from the Complete Concussion Management Inc (CCMI) database, this was a historical cohort study of Canadian athletes aged 12–18 presenting for care early (0–7 days) or late (8–28 days) after SRC. Time-to-recovery was defined as the date of clinician clearance to return to sport. Propensity scores were first derived from logistic regression with early versus late clinical presentation as the outcome. Cox proportional hazards regression analysis was then used to model the relationship between early versus late clinical presentation and time to recovery, while including the propensity score to adjust for confounding. The association was expressed using hazard rate ratios (HRR) with 95% CIs.Results A total of 4696 patient records (mean age of 14.71 (±1.69 SD); 57.7% male) were eligible. Early presentation to a concussion management clinic following SRC was associated with faster time to recovery (adjusted HRR 1.23; 95% CI 1.14 to 1.32, p<0.001). This association was consistent within each quintile of the propensity score. The median time to recovery was 18 versus 22 days in the early and late groups, respectively.Conclusion Adolescent athletes with SRC have favourable recovery trajectories when presenting for care up to 28 days. Time to recovery (clinician clearance to return to sport) may be quicker with an earlier presentation which can lead to a faster return to sport.